Lago Ypacarai: aplicación de tecnosoles antieutrofizantes y reducción de cianobacterias (Journal on studies and research of academic knowledge, 2021)
The results of tests with Technosols to reduce the concentration of nutrients are presented. N (nitrogen) and P (phosphorus) cause eutrophication in the water body of Lake Ypacarai in the central region of Paraguay, located in the National Park Ypacarai Lake. Malpractice in the management of natural resources, inappropriate agricultural practices, discharges of untreated domestic and industrial effluents are loaded with nutrients causing blooms of cyanobacteria and blue green algae. Species detected are Cylindrospermopsis raciborskii, Anabaena spiroides, Aphanocapsa sp., Microcystis aeruginosa, Chroococcus turgidus, Aphanocapsa sp., Anabaena affinis, Aphanocapsa delicatissima, Merismopedia tenuissima and Microcystis flos- aquae. Technosols are inert soils prepared with components similar to those of natural soil. They have higher specific adsorption capacity of organic phosphates and organic solubles and were selected according to the level N and P. A limnocorral of two meters in diameter was installed in the lake for the experiment. Eight kg bags with Technosols were installed at 0.5, 1.0, 1.5, 2.0 and 2.5 meters depth. Our results show that adsorption and ion exchange interact with the adsorbent surfaces, and that they adhere nutrients. Technosols thus permit the reduction of phosphorus in water. A consequence of the adsorption of N and P by Technosols is a strong reduction or even disappearance of some species of cyanobacteria, shown by the laboratory results.
Keywords: Technosols; Lake; Cyanobacteria